2007
DOI: 10.1074/jbc.m607347200
|View full text |Cite
|
Sign up to set email alerts
|

Tristetraprolin (TTP)-14-3-3 Complex Formation Protects TTP from Dephosphorylation by Protein Phosphatase 2a and Stabilizes Tumor Necrosis Factor-α mRNA

Abstract: Tumor necrosis factor (TNF)-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
184
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(194 citation statements)
references
References 52 publications
8
184
1
1
Order By: Relevance
“…Phosphorylation of TTP by MK2 has been suggested to reduce the affinity of TTP for ARE-containing mRNA (7). However, others found that mutation of the two major MK2 phosphorylation sites to alanine had no effect on ARE binding (42). Using purified recombinant TTP and MK2, we also could not detect any difference in affinity of unphosphorylated or phosphorylated TTP for the GM-CSF ARE, showing that regulation of RNA binding does not account for the regulation of deadenylation observed in the in vitro system described here.…”
Section: Discussioncontrasting
confidence: 55%
“…Phosphorylation of TTP by MK2 has been suggested to reduce the affinity of TTP for ARE-containing mRNA (7). However, others found that mutation of the two major MK2 phosphorylation sites to alanine had no effect on ARE binding (42). Using purified recombinant TTP and MK2, we also could not detect any difference in affinity of unphosphorylated or phosphorylated TTP for the GM-CSF ARE, showing that regulation of RNA binding does not account for the regulation of deadenylation observed in the in vitro system described here.…”
Section: Discussioncontrasting
confidence: 55%
“…In addition, the regulation of both subcellular localization and protein stability of mTTP is dependent on MK2 and on the integrity of S 52 and S 178 [53]. Finally, mutation of S 52 to A 52 in mTTP weakly reduces the assembly of TTP-14-3-3, whereas mutation of S 178 to A 178 and of S 52/178 to A 52/178 substantially reduces the association of TTP with 14-3-3 [54].…”
Section: Introductionmentioning
confidence: 99%
“…[162][163][164] Eventually, the phosphatase PP2A binds to and dephosphorylates TTP, facilitating resumption of TTPmediated transcript decay. 158 A similar mechanism may link other kinases to downregulation of RNA destabilizing activity. Gherzi's laboratory has demonstrated that AKT phosphorylates KSRP on serine 193, creating a docking site for 14-3-3.…”
Section: Signaling Pathways and Mrna Turnover Controlmentioning
confidence: 99%
“…Transcript stability is controlled by kinases and other mediators characteristic of cytokine signal transduction pathways, including PKC, [146][147][148][149][150] PKB, 151 MAPK/Erk, 45 PI-3-kinase, 128,152 Src-family kinases, 153 p38 MAPK (reviewed in Dean et al 154 and Kotlyarov and Gaestel 155 ), mixed lineage kinase, 130 JNK kinases, 156,157 and phosphatases such as calcineurin 127 and PP2A. 158 Several of these signaling intermediaries, particularly p38 and ERK have been shown to be important in stabilizing inflammatory transcripts downstream of LPS or IL-1. The example below relates how phosphorylation cascades can lead to stabilization of TNFa in myeloid cells.…”
Section: Signaling Pathways and Mrna Turnover Controlmentioning
confidence: 99%
See 1 more Smart Citation